2023
DOI: 10.1117/1.jbo.28.12.121203
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microstructural investigation of the human tympanic membrane by endoscopic polarization-sensitive optical coherence tomography

Abstract: . Significance Endoscopic optical coherence tomography (OCT) is of growing interest for in vivo diagnostics of the tympanic membrane (TM) and the middle ear but generally lacks a tissue-specific contrast. Aim To assess the collagen fiber layer within the in vivo TM, an endoscopic imaging method utilizing the polarization changes induced by the birefringent connective tissue was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Multiple intraoral OCT scanners on a prototype level have been presented that are applicable for the inspection of the occlusal surface [13,14]. As we have also shown that PS-OCT, e.g., by using a rigid endoscopic setup [15] is in vivo, these results support the way towards an in vivo caries diagnostics based on 3D depolarization imaging.…”
Section: Resultssupporting
confidence: 67%
“…Multiple intraoral OCT scanners on a prototype level have been presented that are applicable for the inspection of the occlusal surface [13,14]. As we have also shown that PS-OCT, e.g., by using a rigid endoscopic setup [15] is in vivo, these results support the way towards an in vivo caries diagnostics based on 3D depolarization imaging.…”
Section: Resultssupporting
confidence: 67%
“…We have recently demonstrated that endoscopic PS-OCT enables the in vivo assessment of the human TM's connective tissue layer based on the retardation contrast. 4 However, we were not able to visualize those collagenrelated signals in all regions of the TM, which is partially explained by the measurement geometry when examining the healthy eardrum through the ear canal. Here, we investigate the existence and accessibility of collagen fibers across the entire TM by PS-OCT of an ex vivo temporal bone specimen and refer it to polarized light microscopic (PLM) images of thin sections, which were excised from the same specimen.…”
Section: Introductionmentioning
confidence: 82%
“…In combination with sound excitation, it is possible to detect vibrations of the ossicles (31) and to evaluate the coupling of middle ear prostheses after a middle ear reconstruction (32). Furthermore, an integration of polarization-sensitive OCT can enable the detection and thickness measurement of the distinct layers of the TM (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although the distorted data are useful to determine the incident angle between beam and surface (see Fig. 4 by Steuer et al [22] for a visualization of the distorted and the corrected data), further calibrations are necessary for an accurate transformation from the spherical coordinate system of the fan-shaped measurement to the final Cartesian representation. Therefore, a 3D-printed calibration target with a plane millimeter grid was measured at the defined working distance of 10 mm.…”
Section: Measurement Systemmentioning
confidence: 99%